Avian Influenza A Virus Polymerase Recruits Cellular RNA Helicase eIF4A3 to Promote Viral mRNA Splicing and Spliced mRNA Nuclear Export - Ren, Xingxing; Yu, Yuandi; Li, Huanan; Huang, Jinyu; Zhou, Aobaixue; Liu, Shukai; Hu, Pingsheng; Li, Bo; Qi, Wenbao; Liao, Ming (Frontiers in Microbiology, 2019)
The influenza A virus replicates in a broad range of avian and mammalian species by hijacking cellular factors and processes. Avian influenza A viruses (AIVs) generally propagated poorly in mammalian cells, but some mutants of virus-encoded RNA polymerase components, especially PB2 subunit, can overcome host restriction. Host factors associated with PB2 may be essential for efficient AIV replication in mammalian cells. Here, we infected human cells with the PB2 Flag-tagged replication-competent recombinant AIV and identified cellular proteins that coprecipitate with PB2 protein by mass spectrometry. We confirmed one of the coprecipitating host factors, DEAD-box protein eIF4A3, that interacts with viral PB2, PB1, and NP proteins. Depletion of endogenous eIF4A3 significantly reduced virus replication. Later studies showed that eIF4A3 is essential for viral RNA polymerase activity and viral RNAs synthesis. Upon systematic dissection of the influenza virus progeny mRNA generation, from pre-mRNA processing to nuclear export, we found that the depletion of eIF4A3 resulted in significant defects in the ratio of M2 to M1 and NS2 to NS1, and the proportion of viral spliced mRNA in the nucleus increased, indicating that eIF4A3 plays a significant function in viral nascent intron mRNA splicing and spliced mRNA (M2 and NS2) nuclear export. Additionally, we confirmed that in specific deletion of eIF4A3, the synthesis of reduced NS2 can significantly impair neo-synthetized viral ribonucleoprotein (vRNP) nuclear export. Taken together, our findings revealed that eIF4A3 is a key mediator of AIV polymerase activity, mRNA splicing, and spliced mRNA nuclear export.